Predictivity of Clinical Findings and Doppler Ultrasound in Pediatric Acute Scrotum - Lemini, Riccardo; Guanà, Riccardo; Tommasoni, Nicola; Mussa, Alessandro; Di Rosa, Gianpaolo; Schleef, Jurgen (Urology Journal, 2016)
Purpose: To evaluate the role of Doppler ultrasonography (DUS) in diagnosing pediatric testicular torsion (TT), and its diagnostic accuracy, and helping clinicians increase specificity and decrease negative exploration rates. Materials and Methods: We performed a retrospective study of all consecutive patients with acute testicular symptoms referring to our pediatric emergency department (ED) from January 2010 to December 2013. Results: We analyzed 1091 patients, with a mean age of 9 years. DUS was performed in 498 patients (40.8%); 107 patients (8.8%) underwent surgery and 41 patients (3.3%) had a TT. The following clinical findings were collected: presence of scrotal pain, erythema and swelling, spermatic cord pain and abnormal cremasteric reflex. The clinical findings significantly associated with TT were spermatic cord pain (OR = 37, 95% CI: 11.9-111.1, P < .001) and abnormal cremasteric reflex (OR = 47.6, 95% CI: 13.5-166.6, P < .001); the presence of swelling resulted confounding (OR = 2.3, 95% CI: 0.7-8.4, P < .001). Scrotal pain was not significantly associated with TT (P = .9), while erythema made TT unlikely (OR = 0.22, 95% CI: 0.07-0.7, P = .0445). In all cases the DUS significantly increased the predictivity. Conclusion: TT was present in 3.3% of patients presenting with testicular symptoms. The predictivity based on clinical findings resulted high and the negative exploration rate for TT was 62%. DUS increased the predictivity in all patients.